2023
DOI: 10.3390/jcm12082846
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Placebo-Controlled Study of a Transcranial Photobiomodulation Helmet in Parkinson’s Disease: Post-Hoc Analysis of Motor Outcomes

Abstract: Emerging evidence is increasingly supporting the use of transcranial photobiomodulation (tPBM) to improve symptoms of neurodegenerative diseases, including Parkinson’s disease (PD). The objective of this study was to analyse the safety and efficacy of tPBM for PD motor symptoms. The study was a triple blind, randomized placebo-controlled trial with 40 idiopathic PD patients receiving either active tPBM (635 nm plus 810 nm LEDs) or sham tPBM for 24 min per day (56.88J), six days per week, for 12 weeks. The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…96,226 In clinical trials, McGee et al found that tPBM (635 nm plus 810 nm LEDs) could safely and meaningfully improve individual motor signs of PD. 33 Hamilton et al developed a helmet device with several LEDs with wavelengths of 670, 810, and 850 nm and reported improvement in PD progression. 31 In fact, owing to the exponential attenuation of light traveling through skull and brain tissues, only a very limited number of neurons can absorb sufficient photons for positive effects.…”
Section: Tpbm For Parkinson's Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…96,226 In clinical trials, McGee et al found that tPBM (635 nm plus 810 nm LEDs) could safely and meaningfully improve individual motor signs of PD. 33 Hamilton et al developed a helmet device with several LEDs with wavelengths of 670, 810, and 850 nm and reported improvement in PD progression. 31 In fact, owing to the exponential attenuation of light traveling through skull and brain tissues, only a very limited number of neurons can absorb sufficient photons for positive effects.…”
Section: Tpbm For Parkinson's Diseasementioning
confidence: 99%
“…In clinical trials, McGee et al. found that tPBM (635 nm plus 810 nm LEDs) could safely and meaningfully improve individual motor signs of PD 33 . Hamilton et al.…”
Section: Tpbm For Brain Diseasesmentioning
confidence: 99%
See 3 more Smart Citations